2014
DOI: 10.1126/science.1250322
|View full text |Cite
|
Sign up to set email alerts
|

A Chloroplast Retrograde Signal Regulates Nuclear Alternative Splicing

Abstract: Light is a source of energy and also a regulator of plant physiological adaptations. We show here that light/dark conditions affect alternative splicing of a subset of Arabidopsis genes preferentially encoding proteins involved in RNA processing. The effect requires functional chloroplasts and is also observed in roots when the communication with the photosynthetic tissues is not interrupted, suggesting that a signaling molecule travels through the plant. Using photosynthetic electron transfer inhibitors with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
234
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(256 citation statements)
references
References 18 publications
(19 reference statements)
11
234
0
Order By: Relevance
“…analyzed the overlapping target genes that are regulated by both phytochrome and chloroplast retrograde signaling pathways and found that there is basically no correlation between these two pathways (Table S5), although they are not mutually exclusive and may coexist and act coordinately in certain conditions, sharing common target genes, such as RS31 (35). GO and other statistical analyses suggested that phytochromemediated control of not only TX, but also AS, have significant roles in light signaling (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…analyzed the overlapping target genes that are regulated by both phytochrome and chloroplast retrograde signaling pathways and found that there is basically no correlation between these two pathways (Table S5), although they are not mutually exclusive and may coexist and act coordinately in certain conditions, sharing common target genes, such as RS31 (35). GO and other statistical analyses suggested that phytochromemediated control of not only TX, but also AS, have significant roles in light signaling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, phytochrome-mediated AS regulation that we demonstrated here seems to be widely conserved in plants. It has been reported very recently that light affects AS of a subset of Arabidopsis genes through a chloroplast retrograde signal, but not through photoreceptor signaling (35). We thus Four-dayold etiolated seedlings were exposed to a 2-min pR (30 μmol·m −2 ·s −1 ), 2-min pFR (60 μmol·m −2 ·s −1 ), pR followed by subsequent pFR (pR/pFR), or were kept in darkness (D).…”
Section: Resultsmentioning
confidence: 99%
“…Proper splicing of these 319 factors was proposed to play a role in the adaptation of the photosynthetic machinery to changes 320 in the light conditions (Petrillo et al, 2014). However, more experimental work is required to 321 identify the components that regulate splicing in response to retrograde signals, the genes 322 affected, and how those changes affect plant development and photosynthetic activity.…”
Section: Higher Order Responses In the Nucleus To Retrograde Signals 316mentioning
confidence: 99%
“…Light has been shown to induce changes in splicing activity (Petrillo et al, 2014;Shikata et al, 317 2014;Hernando et al, 2017) and the splicing pattern of specific splicing factors involved in 318 dark-to-light shifts is regulated in response to the redox status of PET. Proper splicing of these 319 factors was proposed to play a role in the adaptation of the photosynthetic machinery to changes 320 in the light conditions (Petrillo et al, 2014).…”
Section: Higher Order Responses In the Nucleus To Retrograde Signals 316mentioning
confidence: 99%
“…In recent years, forward genetic screens have led to the discoveries that chloroplasts are critical regulators of leaf shape, cell-cell signaling through plasmodesmata, pathogen defense, and even alternative splicing in the nucleus (1)(2)(3)(4)(5)(6)(7)(8); however, in almost all of these pathways, the signaling route between the chloroplast and the nucleus is unknown. This is a pressing question for plant biology and cell biology in general: how do organelles communicate with the nucleus to coordinate genetic programs and cellular function?…”
mentioning
confidence: 99%